Participação da staniocalcina-1 na proteção contra o estresse oxidativo hipocampal e prejuízo a memória em modelo animal de sepse - Bonfante, Sandra Regina Santana Aguiar (2018)
Sepsis still being the main cause of death in ICUs, having a high level of incidence, with elevated costs. During sepsis, the central nervous system (CNS) is one of the first organs to be affected, and this is manifested as sepsis associated encephalopathy (SAE). Objective: This work was aimed to observe the effect of Stanniocalcina-1 over the parameters of oxidative stress in the hippocampus and the memory damage in animals submitted to sepsis by cecal ligation and puncture (CLP). Methods: Male Wistar rats (250-350g) were submitted to the model of sepsis by CLP, with sham animals as a control. The first experimental part divided into sham + saline, CLP + saline and CLP + rhSTC-1 (20, 50 and 100 ng/kg by intracerebroventricular injection. The second experimental part was realized for behavioral evaluation by means of inhibitory avoidance test 10 days after CLP. The animals were divided into sham + saline, sham + rhSTC-1 100ng/kg, CLP + saline and CLP + rhSTC-1 100ng/kg. An N of 12 was used per saline group and an N of 18 was used per CLP group for behavior. The hippocampus was removed 24 hours after surgery. In the hippocampus were evaluated the nitrite and nitrate levels (N/N), oxidative damage to lipids (TBARS), protein carbonylation, and activity of superoxide dismutase (SOD) and catalase (CAT) enzymes. Also, 10 days after sepsis induction, memory and learning of the animals were evaluated. Results: It was verified an increased concentration of N/N in the CLP group with the decrease in the three doses of STC-1. For the lipids damage, we did not find significant results to the treatments, while for the damage to carbonylated proteins, we verified an increase of CLP with the decrease of the dose of 100ng/kg of STC-1. The CAT activity decreased in the CLP group and there was not any change with this treatment while SOD increased its activity in the dose of 100ng/kg of STC-1. In the test de memory by inhibitory avoidance, there was smaller latency in CLP group without treatment with the increase between train and test to STC-1 100ng/kg. Conclusion: The STC-1 attenuates the oxidative stress in the hippocampus of rats submitted to polymicrobial sepsis and influences memory improvement 10 days after sepsis induction.